2018 IEEE International Conference on Communications (ICC) 2018
DOI: 10.1109/icc.2018.8422820
|View full text |Cite
|
Sign up to set email alerts
|

28-GHz Channel Measurements and Modeling for Suburban Environments

Abstract: This paper presents millimeter wave propagation measurements at 28 GHz for a typical suburban environment using a 400-megachip-per-second custom-designed broadband sliding correlator channel sounder and highly directional 22-dBi (15 • half-power beamwidth) horn antennas. With a 23-dBm transmitter installed at a height of 27 m to emulate a microcell deployment, the receiver obtained more than 5000 power delay profiles over distances from 80 m to 1000 m at 50 individuals sites and on two pedestrian paths. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…As shown in Figs. 2 and 3, the minimum directional path loss may even decrease with increasing distance for certain special cases, such as the Route 2 OLoS case in the villa district environment and the OLoS case with the TX-RX separation range of [201,283] m in the industrial park environment, as well as the similar results reported in [5], [21]. This observation implies a strong influence of propagation areas that are sparsely populated with a finite number of scatterers in the characterization of mmWave large-scale fading channels.…”
Section: Azimuth-angle-based Path Loss Characterizationsupporting
confidence: 66%
See 2 more Smart Citations
“…As shown in Figs. 2 and 3, the minimum directional path loss may even decrease with increasing distance for certain special cases, such as the Route 2 OLoS case in the villa district environment and the OLoS case with the TX-RX separation range of [201,283] m in the industrial park environment, as well as the similar results reported in [5], [21]. This observation implies a strong influence of propagation areas that are sparsely populated with a finite number of scatterers in the characterization of mmWave large-scale fading channels.…”
Section: Azimuth-angle-based Path Loss Characterizationsupporting
confidence: 66%
“…In urban microcell and macrocell environments (e.g., urban very-high-rise, urban high-rise, and urban low-rise environments), channel characteristics have been widely investigated in the two 5G mmWave candidate bands (i.e., 28 GHz and 39 GHz) [5]- [8]. However, there is a dearth of research focusing on the underlying measurement-based characterization of mmWave channels in suburban macrocell environments except for [19]- [21]. To predict transmission losses for suburban line-of-sight (LoS) and NLoS scenarios at 28 GHz, directional measured data were collected to fit the close-in (CI) free-space reference distance model and the alpha-beta-gamma (ABG) model, where the antenna pattern was deembedded based on precisely reconstructing the geometric relationship between the antennas [21], [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement system in our previous work [4] was utilized. The receiver (RX), with a chip rate of 399.95 megachips per second, was installed in a backpack and powered by a lithium-ion polymer battery for portability purposes.…”
Section: Measurement Setupmentioning
confidence: 99%
“…These equations are variations of the Friis free-space path loss model, and a few parameters are required [19]. Empirical methods such as the close-in free space reference distance (CI) model and alpha-beta-gamma (ABG) model [4] are relatively easy to handle when the measurement data are given. However, the parameters of empirical models should be determined based on the measurement data collected in a specific scenario and thus their prediction accuracy may decrease when they are applied to a scenario that differs considerably from the measured scenario.…”
Section: Introductionmentioning
confidence: 99%